10th anniversary - Patterson, James 1947-; Paetro, Maxine (New York Grand Central Publishing, 2011)
Detective Lindsay Boxer's long awaited wedding celebration becomes a distant memory when she is called to investigate a horrendous crime: a badly injured teenage girl is left for dead, and her newborn baby is nowhere to be found. Lindsay discovers that not only is there no trace of the criminals, but that the victim may be keeping secrets as well. At the same time, Assistant District Attorney Yuki Castellano is prosecuting the biggest case of her life, a woman who has been accused of murdering her husband in front of her two young children. Yuki's career rests on a guilty verdict, so when Lindsay finds evidence that could save the defendant, she is forced to choose. Should she trust her best friend or follow her instinct? Lindsay's every move is watched by her new boss, Lieutenant Jackson Brady, and when the pressure to find the baby begins interfering with her new marriage to Joe, she wonders if she'll ever be able to start a family
Includes excerpts from Now You See Her and Middle School: The Worst Years of My Life
Best selling thriller author
1
Keywords: Husbands -- Crimes against -- Fiction; Missing children -- Fiction; Public prosecutors -- California -- San Francisco -- Fiction; Teenage girls -- Crimes against -- Fiction; Women detectives -- California -- San Francisco -- Fiction; San Francisco (Calif.) -- Fiction; Mystery fiction; Suspense fiction